Demographic Characteristics in the Usability of the ISBN Online Service in Indonesia - Rahmi, Rahmi; Nabawi, Irham Hanif; Pramono, Hidayat Edi (UI Scholars Hub, 2021)
From 1984 until the present, the National Library of Indonesia has managed the country’s International Standard Book Number (ISBN) system. In 2017, the ISBN online service launched a single account, or access, for which each publisher could register. However, various problems still arise, among them the usability within the ISBN Online system. By collecting responses from 757 respondents who work in publishing companies, this study analyses the relationship between demographic characteristics and a user experience component: usability in the ISBN Online service. The study found five significant relationships such as (1) gender and ISBN Online service design, (2) gender and the service’s ease of use, (3) gender and satisfaction level, (4) age and the service’s ease of use, and (5) work experience and the experience of using ISBN Online. Among other demographic factors, it found that gender is effective at classifying and differentiating usability variable in the ISBN Online service.